Follow-Up of Occupational Health Issues and Measures Taken in Fukushima Daiichi Nuclear Power Plant Where Decommissioning Work Has Continued Over 6 Years Since 2014. Issue 9 (September 2020) - Mori, Koji; Tateishi, Seiichiro; Kubo, Tatsuhiko; Kobayashi, Yuichi; Hiraoka, Ko; Kawashita, Futoshi; Hayashi, Takeshi; Kobashi, Masaki; Kiyomoto, Yoshifumi; Fukai, Kota; Tahara, Hiroyuki; Okazaki, Ryuji; et al.
Abstract : Objectives: To follow up arising occupational health (OH) issues, measures taken, and their performances in the Fukushima Daiichi Nuclear Power Plant since 2014, and thus share experiences and extend the contribution of OH to long-term decommissioning work and preparation for future disasters. Methods: Necessary information from official reports and through the OH-related activities involved was collected and analyzed. Results: The issues were categorized into establishment of the OH management system, three individual issues, and others. During the 6 years until end 2019, the OH management system has been strengthened and OH measures have been enriched gradually by visualizing the broader picture, even though some resistance and problems have been encountered. Conclusions: Improvement in the autonomy of contractors and their ability to respond to environmental changes is necessary.